Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis - Hoskin, Conrad J. (Zootaxa, 2019)
Inland eastern Australia has a complex array of habitats, driven by variation in topography, geology and moisture. This broad region is relatively poorly surveyed compared to coastal eastern Australia and likely contains significant numbers of undescribed reptiles. Oedura monilis is found through much of this region but has been shrouded in taxonomic uncertainty since its original description. Here I assess variation across the range of ‘O. monilis’ and show that it consists of two species: a widespread species in the northern half of the range and a widespread species in the southern half of the range. These two species are readily diagnosed by colour pattern and aspects of shape and scalation. I show that the name O. monilis applies to the northern species. I also show that the name O. attenboroughi Wells & Wellington applies to the northern populations, making it a junior synonym of O. monilis. I describe the southern widespread species as Oedura elegans sp. nov.. I also describe two new, highly localised species from inland eastern Queensland that are allied to O. monilis: Oedura picta sp. nov. from a rocky range in the Moranbah–Dysart region, and Oedura lineata sp. nov. from brigalow forest remnants in the Arcadia Valley. These two species are distinct for colour pattern and aspects of size, shape and scalation. Oedura lineata sp. nov. has a very small and fragmented range, and is restricted to a highly threatened habitat type. It therefore warrants conservation attention. I also provide more detailed diagnoses for O. coggeri Bustard and O. tryoni De Vis, and demonstrate that the name O. ocellata Boulenger is a junior synonym of O. tryoni.